BALEE INONG DAN PENGENDALIAN MASALAH-MASALAH SOSIAL REMAJA (STUDI KASUS DI KECAMATAN ULEE KARENG KOTA BANDA ACEH) - Akmal Saputra (Prodi Sosiologi FISIP Universitas Teuku Umar, 2016)
Banda Aceh has uttered a local institution which was named Balee Inong that was managed by Gampong society (village) especially for woman. Balee Inong has to realize the role of civil society; including tackling the issue of juvenile delinquency, but not specifically institution for handles the issue of juvenile delinquency. One of the problems of juvenile delinquency preventive efforts can be done through education. Based on background of study above, this paper attempts to reveal how is Balee Inong’s effort in instilling the values of education for adolescents who have problems of juvenile delinquency in the district of Ulee Kareng-Banda Aceh? How is Balee Inong’s role in instilling the value of education to mothers in order to fortify and overcome the impact of deviant behavior as well as to educate their children? The theory used in this paper is the Local Institutions by Esman and Uphoff and Social Control Theory. The results showed that the role of women's centers Ceurih to make efforts to handle the problems of juvenile delinquency, carried out through educational patterns or increased capacity and using two methods, the first: through a direct approach, namely the efforts leading to the problems and issues being faced by adolescents; second: through the indirect approach, which attempts to do leads to a skill or capacity-building approach adolescence. Efforts and the roles are not limited to teenagers, but also performed on their mother, in order to fortify and overcome the impact of deviant behavior. Efforts and roles performed are: first, the increase in capacity can be made directly associated with social issues that are occurring with women's expectations of Balee Inong Ceurih can address the problem of juvenile delinquency; second, the majority of programs other capacity building undertaken by Balee Inong Ceurih, actually indirectly also directs women can fortify and tackling deviant behavior. Then, the control of social issues that was conducted by Balee Inong is preventative. Keywords: Balee Inong, social control, juvenile delinquency.